2005
DOI: 10.1007/s00540-004-0299-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose vasopressin infusion in patients with severe vasodilatory hypotension after prolonged hemorrhage during general anesthesia

Abstract: We report the successful use of a low-dose vasopressin (VP) infusion to recover a hypotensive crisis in patients who suffered persistent hypotension after prolonged hemorrhage during general anesthesia. VP was infused in two posthemorrhagic vasodilatory shock patients when they remained persistently hypotensive despite adequate fluid resuscitation and infusions of pharmacological doses of catecholamines. On administration of VP at 0.04 U x min(-1), systemic vascular resistance, systolic arterial pressure, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 13 publications
1
20
0
4
Order By: Relevance
“…Hypotension has been reversed, minimized, or prevented by AVP in patients with septic shock, hypovolemic shock, and refractory hypotension after cardiopulmonary bypass [19,20]. We have reported that pharmacological manipulation of AVP can be beneficial with regard to improved physiological variables and shortterm outcomes in these situations [21,22]. Pharmacological and clinical use of vasodilators Directly or indirectly, blood vessels are the source of many serious diseases that affect millions of people.…”
Section: Hormonal Control In Vsmmentioning
confidence: 98%
“…Hypotension has been reversed, minimized, or prevented by AVP in patients with septic shock, hypovolemic shock, and refractory hypotension after cardiopulmonary bypass [19,20]. We have reported that pharmacological manipulation of AVP can be beneficial with regard to improved physiological variables and shortterm outcomes in these situations [21,22]. Pharmacological and clinical use of vasodilators Directly or indirectly, blood vessels are the source of many serious diseases that affect millions of people.…”
Section: Hormonal Control In Vsmmentioning
confidence: 98%
“…In a porcine model of severe thoracic trauma followed by haemorrhagic shock, arginine vasopressin stabilized arterial blood pressure, cut the amount of fluid resuscitation volume in half, improved pulmonary function, and decreased mortality [31]. This may indicate three beneficial effects of arginine vasopressin in this situation, namely, increasing arterial blood pressure in fluid-refractory and catecholamine-refractory shock [32], shifting blood away from a subdiaphragmatic bleeding site towards the heart and brain (Fig. 1) [33][34][35], and decreasing fluid resuscitation requirements [36].…”
Section: Introductionmentioning
confidence: 95%
“…Auch beim simulierten Thoraxtrauma mit hämorrhagischem Schock konnte mit Vasopressin der Kreislauf stabilisiert und die Letalität gesenkt werden [11]. Diese Beobach tungen aus Forschungslaboren decken sich mit klinischen Erfahrungen bei der Therapie von unkontrollierten hämorrhagischen Schockzuständen in Deutschland, Indien, Japan und Öster-reich [13,26,28,35].…”
Section: Vasopressin Beim Schweren Hämorrhagischen Schockunclassified
“…eine erfolgreiche Defibrillation im traumatischen Kreislaufstillstand ermöglichte [13,19]. Diese Ergebnisse wurden auch von Untersuchern in Deutschland [27], Japan [35] und Indien [28] …”
Section: Erforderliche Patientenzahl Und Dauer Der Studieunclassified
See 1 more Smart Citation